2021
DOI: 10.3390/nu13113960
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Glucans from Fungi: Biological and Health-Promoting Potential in the COVID-19 Pandemic Era

Abstract: Beta-glucans comprise a group of polysaccharides of natural origin found in bacteria, algae, and plants, e.g., cereal seeds, as well as microfungi and macrofungi (mushrooms), which are characterized by diverse structures and functions. They are known for their metabolic and immunomodulatory properties, including anticancer, antibacterial, and antiviral. Recent reports suggest a potential of beta-glucans in the prevention and treatment of COVID-19. In contrast to β-glucans from other sources, β-glucans from mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 194 publications
(266 reference statements)
0
19
0
1
Order By: Relevance
“…Studies have shown that resistant starch potentiates butyrate production and yields more butyrate than non-starch polysaccharides ( 30 , 31 ). Other non-easily digested polysaccharides producing butyrate include cereal breakfasts, such as barley and oats, containing β-glucans, which are also naturally present in edible mushrooms and seaweed ( 32 ). Finally, inulin, on the other hand, is mainly found in artichokes, onion, and chicory roots ( 33 ) are also good foods to increase intestinal butyrate.…”
Section: Sources Of Butyrate In Foodmentioning
confidence: 99%
“…Studies have shown that resistant starch potentiates butyrate production and yields more butyrate than non-starch polysaccharides ( 30 , 31 ). Other non-easily digested polysaccharides producing butyrate include cereal breakfasts, such as barley and oats, containing β-glucans, which are also naturally present in edible mushrooms and seaweed ( 32 ). Finally, inulin, on the other hand, is mainly found in artichokes, onion, and chicory roots ( 33 ) are also good foods to increase intestinal butyrate.…”
Section: Sources Of Butyrate In Foodmentioning
confidence: 99%
“…[2,6]. There is evidence that β-glucan polysaccharides, obtained from mushrooms, possess antiviral activity and could fight against coronavirus SARS-CoV-2 disease (COVID- 19) due to different mechanisms of immunomodulation [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, the priority scientific focus is on β-glucans. Mironczuk-Chodakowska et al [ 56 ] state that β-glucans are natural molecules that have beneficial potential thanks to their immunomodulatory, anti-inflammatory, antineoplastic, antibacterial, antifungal, antioxidant, and anti-allergic antiviral properties. The concentration of β-glucans is several times higher compared to α-glucan.…”
Section: Resultsmentioning
confidence: 99%